Assessment in serious games: An enhanced approach for integrated assessment forms and feedback to support guided learning - AL-Smadi, M.; Wesiak, G.; Guetl, Christian (IEEE, 2012)
Over the last 100 years, the learning process has changed from being repetitive to a new form of learning based on understanding, independency, learners' empowerment and skills improvement. Game-based learning is an example of these new forms of learning in which experiential learning and guided intuitive learning is advocated. As a main part of the learning process, assessment is no more considered to discriminate between students, rather than it is used to enhance students learning and encourage them for further progress and success. In the new era for assessment, students play major roles in the assessment process where they participate in alternative forms of assessment based on their behavior and performance. Moreover, they are provided with timely and quality feedback to scaffold their learning process and to maintain their progress and success. This paper proposes an enhanced approach for assessment in serious games through which instructors can define assessment rules to guide students through dynamic feedback. A proof-of-concept is developed and first findings depict the applicability of providing dynamic assessment and feedback in stealth mode for serious games.